MODEL STORET DAN BEBAN PENCEMARAN UNTUK ANALISIS KUALITAS AIR DI BANTARAN SUNGAI BATU KAMBING, SUNGAI MALI-MALI DAN SUNGAI RIAM KIWA KECAMATAN ARANIO KALIMANTAN SELATAN - Satrio Mantaya; Mijani Rahman; Zairina Yasmi Yasmi (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
This study aimed to analyze the perception of pond fish farmers towards development in the village Minapolitan Cindai Alus and to analysis factors which will affect the development Minapolitan areas such as education, employment, income, length of business, and counseling, especially counseling Fisheries.This study uses a survey approach to the sampling technique used purposive sampling,this is because in this study using a data sample drawn from the population. The type of data obtained in this study is quantitative data, in this study the quantitative data is the data obtained from the perception of fish farmers, communities, and the factors that influence in the form of a score or qualitative data diangkakan. Analysis of the data usinga Likert scale to determine the perception of fish farmers/ community, namely to measure attitudes, income, and perceptions of a person or a group of social phenomena. Multiplelinear regression analysis model is processed through the SPSS program is used to estimate the factors that influence the perception of the development of fish farmers in the village Minapolitan Cindai Alus Martapura Subdistrict Banjar district and the factors that influence it. Factors that influence public perception of the pond fish farmers in the village minapolitan program Cindai Alus Martapura Subdistrict Banjar district namely Education, Income, Old Business, and Education. The results of t-test education amounted to 3,912 with significance level of 0.001. The results of t-test income amounted to 0.189 with a significance level of 0.853. T-test results for long operations amounted to 0.331 with a significance level of 0.745. The results of t-test counseling is at 0.318 with asignificance level of 0.775.